Morphology and sexual dimorphism of the New Caledonian Crow Corvus moneduloides, with notes on its behaviour and ecology - Kenward, B; Rutz, C; Weir, A; Chappell, J; Kacelnik, A (2004)
New Caledonian Crows Corvus moneduloides are known to be extraordinary tool makers and users, but little is known of other aspects of their biology. Here, we report recent field observations of their behaviour and ecology, along with measurements of 19 morphological traits and two flight performance parameters taken from 22 captured Crows. These measurements showed that the Crows were sexually dimorphic in size (the males were larger) but not in shape. We also found that the crows lived in mixed-sex groups, and we observed juvenile-type begging behaviour and feeding by regurgitation, which supports the hypothesis that these may be family groups.